COMBINE HARVESTER'S HEADER PART PRELIMINARY ADJUSTMENT SUBJECT DOMAIN MODELLING - L.V. BORISOVA; N.M. SERBULOVA (Advanced Engineering Research, 2009)
Subject domain's Combine header part preliminary adjustment fuzzy expert knowledge representation some aspects are considered. Subject domain's offered model forms a basis of base of knowledge еxpert system on technological service of combines.